Sports and Social Transformation: A Conceptual Framework for Inclusive Growth - Rajeev; Singh, Damanpreet (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Sports play a vital role in shaping societies by promoting equality, inclusion, and collective identity. This paper examines the role of sports as a medium of social transformation and proposes a conceptual framework for inclusive growth. Drawing insights from social theories such as Social Capital Theory and Functionalism, the paper explains how sports foster community integration, reduce discrimination, and encourage social mobility. It further highlights the significance of sports in gender equality, youth development, and cultural exchange. The paper concludes with recommendations for policymakers and educators to use sports as a tool for inclusive social development.